Determinants of OVO Mobile Payment Adoption among Generation Y and Z Users in Indonesia: The Mediating Role of Satisfaction - Nuri Aslami; Ali Ikhwan; Ismail Lutfi Japakiya (Global Research Collaboration, 2026)
Understanding the factors influencing mobile payment acceptance has become increasingly crucial amid the rapid expansion of digital payment systems in Indonesia. Using satisfaction as a mediating variable, this study integrates the Technology Acceptance Model (TAM) and the Theory of Reasoned Action (TRA) to investigate OVO mobile payment acceptance among Generation Y and Generation Z users in Indonesia. A total of 165 active OVO users participated in an online survey as part of a quantitative approach. Structural Equation Modeling Partial Least Squares (SEM-PLS) was used to examine the data. The findings show that perceived usefulness and convenience of use do not significantly affect satisfaction or intention to use. In contrast, features and trust significantly influence satisfaction, and satisfaction significantly and positively affects intention to use. Additionally, full mediation is indicated by the feature's substantial indirect effect on intention to use via satisfaction. Partial mediation is indicated by the direct and indirect effects of trust on intention to use, mediated by satisfaction. These results show that trust, application features, and user pleasure are more important among digitally aware generations than basic technology acceptance considerations. By illustrating the mediating function of pleasure in explaining OVO adoption behavior among Generation Y and Generation Z users in Indonesia, this study adds to the literature on mobile payment acceptance. Practically, OVO providers should focus on strengthening application features, maintaining user trust, and improving customer satisfaction to encourage continuous usage intention.